PELAPORAN PROGRAM KEMITRAAN DAN BINA LINGKUNGAN SERTA CORPORATE SOCIAL RESPONSIBILITY BADAN USAHA MILIK NEGARA - Fajar, Mukti; Budi Setyaningrum, Reni (Jurnal Media Hukum, 2017)
Act number 13 of 2003 on State Owned Enterprise obligate State Owned Enterprise to pay attention on social issues through Partnership and Community Development Program (PKBL). Meanwhile Act number 40 of 2007 on the Limited Liability Company instruct Limited Liability Company to implement Social and Environmental Responsibility which often called as Corporate Social Responsibility (CSR). These two programs are practically have almost the same form, thus assign a double burden for SOEs on its implementation. This study aims are to find out the mechanism of implementation and reporting of PKBL and CSR from SOEs which are both regulated in different legal regimes. This research is conducted normatively by reviewing various rules and legal documents and empirically by assessing various implementation of PKBL and CSR by SOEs. The result of this study indicate that SOEs must perform PKBL if they have profits, while SOEs related to natural resources industry have to implement CSR which obtained from company’s budget. Both programs are implemented in the same form in providing social assistance and community business. The CSR report is only reported in the Company's annual report to be accounted in front of General Meeting of Shareholders. While the aims of Partnership and Community Development Program financial reporting is to provide information on financial position, activity and cash flow statement and records, for stakeholder’s decision making.